The Influence of Work Motivation, Psychological Empowerment, and Perceived Organizational Support on Job Satisfaction Among Hospital Employees - Jasmine Syabania Noviantri; Agustinus Purna Irawan (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of work motivation, psychological empowerment, and perceived organizational support on hospital employees’ job satisfaction, both partially and simultaneously. Job satisfaction is one of the important factors that affect employee performance and the quality of hospital services. Therefore, it is necessary to understand the factors that can enhance employee job satisfaction so that organizations can create a productive and sustainable work environment. This study employed a quantitative approach by collecting data through questionnaires distributed to hospital employees. The data obtained were analyzed using multiple linear regression techniques to examine the relationships among the research variables. The results indicate that work motivation has a positive and significant effect on employee job satisfaction. Psychological empowerment was also found to have a positive and significant effect on job satisfaction and emerged as the most dominant variable. In addition, perceived organizational support has a positive and significant effect on employee job satisfaction. Simultaneously, work motivation, psychological empowerment, and perceived organizational support were proven to have a significant effect on the job satisfaction of hospital employees. These findings suggest that improving job satisfaction can be achieved through strengthening work motivation, enhancing employees’ psychological empowerment, and providing continuous organizational support. Therefore, hospital management should develop policies focused on improving employee welfare, participation, and development in order to support optimal service quality.